THE SOCIAL PERSONALITY AUTONOMY COMPETENCE AMONG JUNIOR HIGH-SCHOOL STUDENTS - Juster Donal Sinaga (Sanata Dharma University Yogyakarta, 2017)
The autonomy competence in the social personality of the adolescents became one of the development aspects which must be urgently acquired by adolescents. Failure to be autonomous in the social personality during the adolescence period would have bad impact in the subsequent ages. The aims of the research were (1) to describe the level of autonomy competence of social personality in one of private Junior High schools, (2) to identify the items of the Inventory of Adolescent Social Personality Autonomy Competence (IASPAC) in the low and very low categories as the base to propose the topics of social personality guidance in one of the private junior high schools in Yogyakarta. The research subjects were the 141 students in grades VII, VIII, and IX. The research instrument was Inventory of Adolescent Social Personality Autonomy Competence (IASPAC) numbering 39 items which were composed by the researcher on the ground of the autonomy competence standards in the American School Counselor Association (ASCA) model, at the reliability value of 0.935. The data analysis was descriptive analysis with the categorization of the average numbers. The research result showed that as a whole the autonomy competence in the social personality of the students in one of the private junior high-schools in Yogyakarta was categorized as ‘autonomous’, with the following details, 18 students (12.7%) were categorized as ‘very high’, 104 students (73.7%) were categorized as ‘high’, 19 students (13.48%) were categorized as ‘medium’, and none of the students were categorized as ‘low’ and ‘very low’. There were many differences in the average of the social personality autonomy competence among the grade VII, VIII, and IX students. The grade VII students’ level of social personality autonomy competence was higher than that of the grade VIII and IX students. The other finding was that there were 10 items of the IASPAC with the lowest scores. These items would be used as the basis to propose topics for classical guidance of the social personality.